Trinuclear Cyanido‐Bridged [Cr2Fe] Complexes: To Be or not to Be a Single‐Molecule Magnet, a Matter of Straightness. Issue 62 (5th October 2021) - Pichon, Céline; Suaud, Nicolas; Jubault, Valentin; Duhayon, Carine; Guihéry, Nathalie; Sutter, Jean‐Pascal
Abstract: Trinuclear systems of formula [{Cr(L N3O2Ph )(CN)2 }2 M(H2 L N3O2R )] (M=Mn II and Fe II, L N3O2R stands for pentadentate ligands) were prepared in order to assess the influence of the bending of the apical M−N≡C linkages on the magnetic anisotropy of the Fe II derivatives and in turn on their Single‐Molecule Magnet (SMM) behaviors. The cyanido‐bridged [Cr2 M] derivatives were obtained by assembling trans ‐dicyanido Cr III complex [Cr(L N3O2Ph )(CN)2 ] − and divalent pentagonal bipyramid complexes [M II (H2 L N3O2R )] 2+ with various R substituents (R=NH2, cyclohexyl, S, S ‐mandelic) imparting different steric demand to the central moiety of the complexes. A comparative examination of the structural and magnetic properties showed an obvious effect of the deviation from straightness of the M−N≡C alignment on the slow relaxation of the magnetization exhibited by the [Cr2 Fe] complexes. Theoretical calculations have highlighted important effects of the bending of the apical C−N−Fe linkages on both the magnetic anisotropy of the Fe II center and the exchange interactions with the Cr III units. Abstract : Cyanido‐bridged trinuclear [Cr III 2 Fe II ] complexes were investigated in order to assess the influence of the bending of the apical Fe−N≡C linkages on their SMM behaviors. A comparative examination of the structural and magnetic properties showed an obvious effect of the deviation from straightness of the M−N≡C alignment on the slow relaxation of the magnetization exhibited by the complexes. Theoretical calculations have highlighted important effects on both the magnetic anisotropy of the Fe II center and the exchange interactions with the Cr III units.